Quilt, shame and internalized stigmatization in alcohol addicts - Çam, Olcay; Ayakdaş Dağlı, Dilek (Journal of Dependence, 2017)
Internalized stigmatization; is the cognitive and affective internalization of the patient's who stigmatized by society. The individual begins to see himself/herself as if he/she is stigmatized by others, and causes guilt, shame, feelings of inferiority, deterioration in family and friendship relationships and a decrease in selfesteem. Negative emotions are occured in person who internalized the stigma. The more important of these emotions are guilt and shame. Individuals who live with feelings of guilt and shame tend to drink alcohol as a way of coping with these emotions. After consuming alcohol, person experiences the feelings of guilt and shame again. This vicious circle, adversely affects the treatment of patients and increases relapse. Therefore, coping with these emotions, specially guilt and shame, are important component for alcohol addiction treatment. In the light of these information, the aim of this article is to take an attention the importance of internalized stigmatization, guilt and shame in alcohol addicts.
Keywords: Alcohol; Shame; Quilt; İnternalized Stigma